Environmental Conservation in non-Hazardous and Toxic Waste Management Program at Company Unit of PT Pertamina Patra Niaga Region Sumbagut - Andi Ricoh Aditya Mahendra; Teguh Try Hartono; Riky Ismed; Vander Hens Lumban Tobing; Dedi Krismanto; Roni Riski Januari Pandiangan; Azman (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2023)
This study aims to introduce the initiatives undertaken by various divisions within PT Pertamina Patra Niaga Region Sumbagut in effectively managing non-B3 waste with a focus on environmental preservation. Qualitative methods and participatory action research techniques were employed to achieve this objective. The findings of this research demonstrate that non-hazardous solid waste is mitigated through digitization and repurposing. Digitization is applied to paper waste to prevent accumulation, while repurposing involves converting organic, plastic, and rubber waste into reusable objects. Both waste management models prioritize environmental conservation and lead to cost savings. The efficient utilization of non-B3 solid waste serves as an exemplary approach to minimizing waste impacts throughout various activities, underscoring a strong commitment to environmental preservation.